Narrativas digitales y representación de género en territorios periféricos: el pódcast como estrategia de visibilización sociocultural en Arauca (REVISTA NODO, 2025)
This article delves into the use of podcasts as an alternative communication tool to highlight women's participation in the political and cultural spheres of Arauca, Colombia. Through the audio production *Alma Llanera, Voz de Mujer* (Soul of the Plains, Woman's Voice), the possibilities of journalism for constructing inclusive narratives from peripheral territories are explored. These territories are characterized by social and cultural dynamics marked by patriarchal structures and low female representation in traditional media. The audio production serves as a foundation for academic reflection; it was developed using a qualitative methodology, combining documentary research and semi-structured interviews with women leaders from the municipality of Arauca. These interviews were then analyzed in light of theoretical frameworks on communication for
Keywords: comunicación de masas; mujer y desarrollo; cultura tradicional; política y gobierno; periodismo; pódcast